Repression: Psychoanalytic and Sartrean Phenomenological Perspectives (Existential Analysis: Journal of the Society for Existential Analysis, 2010)
Freud's psychoanalysis places repression in the unconscious, working as a mechanical process devoid of awareness, whereas Sartre's phenomenology insists that this repression is entirely conscious and transparent. What, then, might be happening in terms of mental events analysable as either unconscious censorship or conscious denial? This paper investigates what can and cannot be ascribed as unconscious concerning the 'mechanism' of repression and raises questions about the ontology of the unconscious. Is the unconscious an invisible domain or, more simply, aspects of more skilfully created absences within our being? Implications for psychopathology and therapy are suggested where the Sartrean view is taken into account.